"There remains nothing to lose for the one who has lost liberty": liberty and free will in Arcangela Tarabotti's (1604–1652) radical criticism of the patriarchy. Issue 1 (2nd January 2021) - Ebbersmeyer, Sabrina
ABSTRACT: This article examines the concepts of liberty and free will in Arcangela Tarabotti's work Paternal Tyranny (1654) and the role these concepts play in Tarabotti's criticism of the patriarchy. It is argued that liberty is a key concept, through which the radical nature of the treatise becomes apparent. The first part reconstructs Tarabotti's understanding of women's liberty and free will and its theological and political implications (2). Based in this analysis, it is evident that Tarabotti exposes the disregard of women's free will and liberty as sacrilege in relation to God and ecclesiastical institutions and as tyranny in relation to women and political institutions (3). The following part reconstructs Tarabotti's tackling of the impediments of women's free will in the family, the church, and the state. It is shown that Tarabotti politicized and criminalized well-established practices of women's suppression in society (4). The last part provides evidence that Tarabotti's treatise was considered to be politically dangerous, which caused insurmountable problems for publishing the work in Italy and France and eventually led to the condemnation of the work once it was published in Holland. The article concludes that Tarabotti's text should be read as a radical political treatise (5).